2023
DOI: 10.1126/sciadv.adf7704
|View full text |Cite|
|
Sign up to set email alerts
|

Societies of strangers do not speak less complex languages

Olena Shcherbakova,
Susanne Maria Michaelis,
Hannah J. Haynie
et al.

Abstract: Many recent proposals claim that languages adapt to their environments. The linguistic niche hypothesis claims that languages with numerous native speakers and substantial proportions of nonnative speakers (societies of strangers) tend to lose grammatical distinctions. In contrast, languages in small, isolated communities should maintain or expand their grammatical markers. Here, we test these claims using a global dataset of grammatical structures, Grambank. We model the impact of the number of native speaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…More specifically, [ 56 ] also found an inverse correlation between exotericity and morphological complexity. On the other hand, a very recent, comprehensive study reported in [ 57 ] denies the significance of any correlations between linguistic and societal factors pertaining to esotercity/exotericity, claiming only a weak effect, and concluding in their title that “Societies of strangers do not speak grammatically simpler languages.” As obvious already from this title, their study has a very different overarching hypothesis from ours, and our two studies are thus not directly comparable, even if they look at very similar phenomena, and pose very similar questions. First, their hypothesis is that any type of grammatical complexity (including morphological and syntactic) correlates inversely with societal exotericity, which is in direct opposition to our hypothesis for syntax.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, [ 56 ] also found an inverse correlation between exotericity and morphological complexity. On the other hand, a very recent, comprehensive study reported in [ 57 ] denies the significance of any correlations between linguistic and societal factors pertaining to esotercity/exotericity, claiming only a weak effect, and concluding in their title that “Societies of strangers do not speak grammatically simpler languages.” As obvious already from this title, their study has a very different overarching hypothesis from ours, and our two studies are thus not directly comparable, even if they look at very similar phenomena, and pose very similar questions. First, their hypothesis is that any type of grammatical complexity (including morphological and syntactic) correlates inversely with societal exotericity, which is in direct opposition to our hypothesis for syntax.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the syntactic parameters that we consider are much more fine-grained. Whereas the advantage of [ 57 ] is in its statistical power, our approach enables us to get more specific in identifying syntactic and morphological aspects of language variation that pertain to esotericty/exotericity, as well as to outline what further research is needed to shed light on this question. To take just one example, we consider the presence of definite and indefinite articles to be much more relevant for syntactic complexity than having a politeness distinction in pronouns, both of which are considered as equally relevant in [ 57 ] (see p.4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, depending on how you count, there are between 6000 and 8000 different languages and language varieties on the planet 13 – 15 that vary widely in their structural properties 16 , 17 . A growing body of cross-linguistic research has begun to document that the natural and social environments in which languages are being used and learned drive this diversity 18 21 , that language structure is influenced by socio-demographic factors such as the estimated number of speakers 18 , 21 23 and that the long-held belief in a principle of "invariance of language complexity" 24 may be incorrect 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, previous research 21 , 36 – 42 has shown that cross-linguistic (and cross-cultural) studies that seek to analyse potential statistical associations between language features and external factors must take into account Galton's problem, which refers to the potential confounding of linguistic and cultural similarities by phylogenetic relatedness and geographical proximity. To address this issue, we take a comprehensive approach, using both established analytical methods 41 and novel quantitative techniques developed in the field of econometrics that leverage machine learning 43 , 44 and spatial autoregressive models 45 .…”
Section: Introductionmentioning
confidence: 99%